Discrepancy in the Distribution Patterns of Subchondral Bone Density Across the Ankle Joint After Medial Opening-Wedge and Lateral Closing-Wedge High Tibial Osteotomy. Issue 2 (February 2022) - Matsubara, Shinji; Onodera, Tomohiro; Iwasaki, Koji; Hishimura, Ryosuke; Matsuoka, Masatake; Kondo, Eiji; Iwasaki, Norimasa
Background: High tibial osteotomy (HTO) changes the alignment and dynamics of the ankle joint; however, differences in the stress distribution of the ankle joint after opening-wedge HTO (OWHTO) and closing-wedge HTO (CWHTO) are not understood. It is believed that subchondral bone density of the articular surface reflects the pattern of cumulative stress distribution across the joint surface. Purpose: To clarify the effects of OWHTO and CWHTO on the distribution patterns of subchondral bone density across the ankle joint using computed tomography (CT)–osteoabsorptiometry. Study Design: Cohort study; Level of evidence, 4. Methods: Radiographic and CT data of 18 cases who underwent OWHTO (OW group), 12 cases who underwent CWHTO (CW group), and 11 cases with unilateral anterior cruciate ligament injury serving as controls were retrospectively reviewed. The subchondral bone density of the distal tibia was assessed in the 3 groups using CT-osteoabsorptiometry. The distal tibial surface of the ankle joint was divided into 4 parts in the coronal direction, and the percentage of the high-density area (%HDA) to each subregion was compared before and after HTO. Results: Preoperatively, comparing %HDA among the 3 groups, there were no significant differences in any regions. In the OW group, postoperative %HDA in the most medial region was significantly increased compared with preoperative %HDA (49.3% to 53.0%; P = .011), and postoperative %HDA in the most lateral region was significantly decreased (21.4% to 17.2%; P = .003). On the other hand, in the CW group, postoperative %HDA in the most medial region was significantly decreased (55.7% to 35.7%; P = .001), and %HDA in the second lateral region was significantly increased (23.6% to 29.2%; P = .002). Conclusion: The ankle distribution pattern of subchondral bone density shifted significantly medially after OWHTO without fibular osteotomy, whereas the distribution pattern shifted laterally after CWHTO with fibular osteotomy. When the OWHTO is performed for patients with medial ankle osteoarthritis, surgeons should pay attention to potential postoperative progression of ankle osteoarthritis due to medial shift of the stress distribution in the ankle joint.